Comparative study of total abdominal hysterectomy, vaginal hysterectomy and laparoscopic assisted vaginal hysterectomy - P V Ramana Bai; K Lakshmi Devi (MRIMS Journal of Health Sciences, 2016)
Background: In 1934, Heaney 1st reported vaginal hysterectomy with few modifications and this method is favoured commonly in the preset days. In the early decades of 20th century, hysterectomy began to be used more often in the treatment of gynecologic disease and symptom. As the surgery became safer, skillfull gynecologists concentrated on developing newer surgical procedures to help the patients. Note worthy contributors were more to the techniques of gynecologic surgery by Sims, Werthieins, Schauta, Kelly, Clarhe, Mayo, Meigs and many others. Objective: To compare total abdominal hysterectomy, vaginal hysterectomy and laparoscopic assisted vaginal hysterectomy. Methods: In this study, 90 cases of hysterectomy were analyzed over a period of two years for comparison between abdmonial, vaginal and laparoscopic assisted vaginal hysterectomies. Of which 30 were abdominal, 30 were simple vaignal and remaining were LAVH. Results: LAVH took longer operative time i.e. around 120 minutes when compared to TAH and VH. TAH & VH took almost same operative time without much difference. In the present study associated intra operative problems were observed in 7.7% of cases. In the present study, 6.6% of cases were associated with cystic ovaries and among them most of them underwent TAH. We found that 6.6% of women had hemorrhage in TAH and 3.3% in VH. The incidence of bladder injury was 1.1% in the present study. Parker RB et al found bladder injury in 0.67%. One patient had bowel injury due to multiple adhesions which is recognized on 3rd post operative day and laparotomy was done. Conclusion: Among all three methods of hysterectomies the preferable method of choice is vaginal hysterectomy and LAVH is the second method of choice and the abdominal route is last choice.